2016
DOI: 10.1016/j.jclepro.2016.08.079
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic life cycle assessment of a lightweight solution for an automotive component: A comparison between talc-filled and hollow glass microspheres-reinforced polymer composites

Abstract: Overall, light weighting strategies are mainly analysed in the aim of reducing impact during the use phase of a vehicle. In this paper environmental and economic assessments are combined to evaluate the sustainability of adopting an innovative lightweight material for an automotive component. The analysis is carried out according to the Life Cycle Assessment and Life Cycle Costing methods. A standard solution, based on talc filler-reinforced composite, and an innovative one made with hollow glass micro-spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 43 publications
0
50
0
2
Order By: Relevance
“…Delogu and coworkers 9 combined environmental and economic assessments to evaluate the usage of talc and HGM as reinforcing agents in polymer composites used as lightweight materials in automotive components. The authors observed that based both on environmental and economic assessments HGM-reinforced polymer composites are preferable to talc filler-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Delogu and coworkers 9 combined environmental and economic assessments to evaluate the usage of talc and HGM as reinforcing agents in polymer composites used as lightweight materials in automotive components. The authors observed that based both on environmental and economic assessments HGM-reinforced polymer composites are preferable to talc filler-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the fundamental variables of the economic model implies the definition of the LCC of the project [26,47] and the estimation of the annual sales. Please note that we obtained the estimated costs and estimated annual sales included in the economic feasibility procedure for tidal energy projects (TEPs) by carrying out an analysis of current scientific literature and reports created by companies that specialize in these types of technologies and shipyards.…”
Section: Study Of the Costs Throughout The Service Life Of The Projecmentioning
confidence: 99%
“…Research on automotive industry is also dedicated to investigate green or sustainable supply chain management practices and to develop models [12][13][14][15]. Life cycle assessments for automobile components such as exterior door skin [16], multi-material component for brake system [17], composite material for vehicle dashboard [18] were also undertaken. Limited studies exist on the solid wastes from automotive industry and their management.…”
Section: Introductionmentioning
confidence: 99%